ANALISIS MASALAH KESENJANGAN SOSIAL DI SEKOLAH DASAR - Maharani, Nabilah; Khoirunnisa, Nabila; Putri, Shabira Panca (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research is entitled Analysis of Social Gap Problems in Elementary Schools. The purpose is to analyze the problem of social inequality in primary schools, especially in SD Negeri 01 and 04 Desa Berkat. The method of analysis is to use a qualitative approach through interview, observation, and documentation methods. The results showed that there is a social gap in primary schools, reflecting inequity in access to education between students in urban and remote areas. Factors such as the low quality of school facilities, the low quality of teachers, the high cost of education and the lack of infrastructure influence this inequality. This condition is exacerbated by inequitable education policies, creating unequal educational opportunities for all levels of society. To overcome this problem, serious efforts are needed from the government and society to improve the quality and accessibility of education in all regions, to ensure equal education rights for every child of the nation.